Analyzing Thrifting Legality and Tax Compliance Through a Social Science Education Perspective - Mohammad Ilham Prasetyo; Evan Novika Ramdhani (Yayasan Cerdas Pedia Indonesia, 2025)
The resurgence of illegal thrifting in Indonesia persists despite strict prohibitions under Minister of Trade Regulation Number 40 of 2022, creating a conflict between market demand and state sovereignty. This study analyzes the intersection of trade legality, tax compliance, and educational intervention using normative juridical and socio-pedagogical methods. Findings indicate that aggressive enforcement fails to address the root cause: irrational consumer behavior. Although traders seek legitimacy through tax payments, the government maintains that fiscal compliance cannot validate prohibited imports. Structural Equation Modeling reveals that